2006
DOI: 10.1007/s00381-006-0080-0
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic macrocephaly in the infant: long-term neurological and neuropsychological outcome

Abstract: Prospective review studies such as this indicate that abnormal radiological findings in infancy are not necessarily predictive of neurodevelopmental problems and may reflect a normal variant. However, while overall intellectual ability may be within average limits in this diagnostic sample, considerable individual variations remain in specific areas of neuropsychological function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 20 publications
3
45
0
1
Order By: Relevance
“…2 Enlarged SS typically normalize by 2-3 years of age in BESS. 2,22,37 The patients with macrocrania and normal SS in our study may be at the later stages of this condition. There are some limitations to this study.…”
Section: Discussionmentioning
confidence: 67%
“…2 Enlarged SS typically normalize by 2-3 years of age in BESS. 2,22,37 The patients with macrocrania and normal SS in our study may be at the later stages of this condition. There are some limitations to this study.…”
Section: Discussionmentioning
confidence: 67%
“…One such study by Muenchberger et al [23] found that 4/9 BEH patients evaluated with imaging and full neuropsychiatric testing an average of 15 years after initial diagnosis demonstrated problems with tests of attention, sequencing and visual motor scanning, functions that are generally attributed to the frontal lobe. However, the authors concluded that the overall intellectual abilities of the study group as a whole were within normal range.…”
Section: Discussionmentioning
confidence: 99%
“…The subtype “external hydrocephalus” is usually defined as a rapid increase in head circumference, combined with enlarged subarachnoid spaces as seen on neuroimaging—especially overlying the frontal lobes—and normal or only moderately enlarged ventricles [4, 91, 105, 118, 140, 143]. It occurs mainly during infancy, and the subarachnoid space enlargement gradually decreases and disappears over the next years [91, 110, 118].…”
Section: Introductionmentioning
confidence: 99%